Layer-by-layer self-assembled nanofiltration membrane as well as preparation method and application thereof
By alternately coating large-molecular and small-molecular-weight polyelectrolytes on high-porosity and large-pore size base films, the problem that nanofiltration membranes are difficult to have high interception performance when improving permeability is solved, and efficient water separation and micropollutant removal are achieved.
Patent Information
- Application Number
- CN202411850204.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In the prior art, it is difficult for the nanofiltration membrane to have high retention properties when improving permeability. Especially when the base membrane pore size is large, traditional layer-layer self-assembly methods cannot effectively prepare high-performance nanofiltration membranes.
By first forming a large molecular weight cationic polyelectrolyte layer on a base film with high porosity and large pore size, and then forming a small molecular weight anionic polyelectrolyte layer, the initial alternating coating and separation alternating coating are constructed to ensure the structure and performance of the nanofiltration membrane.
The nanofiltration membrane has achieved both high permeability and high interception performance. The pure water permeability coefficient reaches 15L/m2·h·bar, the interception rate of MgSO4 reaches more than 95%, and the process is simple and the cost is low.
Smart Images

Figure CN119565398A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nanofiltration membrane, in particular to a layer-by-layer self-assembled nanofiltration membrane and a preparation method and application thereof. Background Art
[0002] Nanofiltration membrane (NF membrane for short) is a new membrane separation technology between reverse osmosis and ultrafiltration. Under the driving force of pressure difference, nanofiltration membrane allows salt and small molecules to pass through the nanofiltration membrane, while retaining macromolecules. It is a separation membrane that can efficiently remove substances with a number average molecular weight of 200-1000Da or more, and is mainly used for the concentration and purification of macromolecules in solution. Layer-by-layer self-assembly technology (LBL) is a technology for preparing multilayer nanofilms: two or more assembly materials are coated on a substrate in sequence, and the coating process can be repeated as needed. The driving force for the assembly of polyelectrolyte multilayer membranes is the entropy increase of oppositely charged polyelectrolytes during the pairing process. The water-soluble linear polyelectrolytes used in LBL can form interconnected, highly permeable nanopore channels with adjustable pore size, and have low operating pressure and high water recovery rate. It is one of the most effective technologies for removing micropollutants and separating ions.
[0003] The preparation of the core structure of the layer-by-layer self-assembled NF membrane requires two materials: a base membrane and a coating polyelectrolyte. For the base membrane, a high surface porosity generally means that the membrane pores are relatively large. For polyelectrolyte composite nanofiltration membranes, experiments have verified that small molecular weight polyelectrolytes are more likely to fill the pores of the base membrane, thereby improving the filling to form a thinner and denser separation layer, and improving the retention rate of the NF membrane for the target removal molecules. In aqueous solution, small molecular weight polyelectrolytes are spherical and can improve the retention rate of the NF membrane for the target removal molecules. Patent CN 102580550 B discloses a method for preparing a nanofiltration membrane using oppositely charged polyelectrolytes alternately deposited on the surface of an ultrafiltration membrane. The base membrane MWCO used is 50kDa, and the permeability of the prepared NF membrane is 5.1-7.8L / m 2 ·h·bar, and the Na2SO4 rejection rate is 91%. Patent CN 102688701 A discloses a NF membrane with a permeability of 3.0-7.4L / m 2 ·h·bar, the rejection rate of Na2SO4 reached 90%. Although some previous research methods can prepare NF membranes with high rejection performance for divalent salt ions, such as PSS / PAH coating on a base membrane with a MWCO of 65Da, the rejection rate of Mg 2+ , Ca 2+ and Sr 2+NF membrane with a retention rate between 97.7% and 99.5% (Desalination 534 (2022) 115793); PSS / PAH was coated on a base membrane with a MWCO of 52 kDa to obtain a Mg 2+ NF membranes have a rejection rate of up to 99.9% (Journal of Membrane Science 663 (2022) 121027), but the permeability of these NF membranes is difficult to increase to 10 L / m 2 ·h·bar, the PAH / PSS coating on the base membrane with MWCO of 113kDa increased the permeability to 12L / m 2 ·h·bar, but Mg 2+ The retention rate slightly decreased to 94.1% (Desalination 574 (2024) 117229). These experimental results prove that high porosity and large pore size base membranes can improve the permeability of LBL NF membranes, but will sacrifice the compactness of the cortex, resulting in a possible decrease in the retention rate of the NF membrane. The literature reported that when the base membrane MWCO was 500kDa and 500kDa, no Na2SO4 retention performance was observed even after 10 double layers were coated (Langmuir 21 (2005) 10587-10592), indicating that the traditional layer-by-layer self-assembly method cannot prepare a NF membrane with high retention performance by coating on a base membrane with a pore size that is too large. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a layer-by-layer self-assembled nanofiltration membrane and a preparation method and use thereof, so as to solve the problem that the nanofiltration membrane in the prior art cannot meet the performance requirements.
[0005] To achieve the above-mentioned purpose and other related purposes, the present invention is implemented by including the following technical solutions.
[0006] The present invention provides a layer-by-layer self-assembled nanofiltration membrane, which comprises a base membrane and a self-assembled coating formed on the base membrane, wherein the self-assembled coating at least comprises an initial alternating coating and a separation alternating coating; the base membrane has a molecular weight cutoff of not less than 500 kDa; the initial alternating coating is an alternating assembly of a large molecular weight cationic polyelectrolyte layer and an anionic polyelectrolyte layer, and the separation alternating coating is an alternating assembly of a small molecular weight cationic polyelectrolyte layer and an anionic polyelectrolyte layer; the initial alternating coating is formed on the base membrane, and the large molecular weight cationic polyelectrolyte layer in the initial alternating coating is a cationic polyelectrolyte with a number average molecular weight of not less than 500 kDa; the small molecular weight cationic polyelectrolyte layer in the separation alternating coating is a cationic polyelectrolyte with a number average molecular weight not exceeding 100 kDa.
[0007] In the technical solution of the present application, the molecular weight of the polyelectrolyte has a direct impact on the structure of the nanofiltration membrane, such as the pore size and morphology of the separation functional layer, and thus ultimately affects the performance of the nanofiltration membrane. Specifically, a suitable high molecular weight polyelectrolyte layer is first formed on a high porosity, large pore size base membrane, and then a suitable low molecular weight polyelectrolyte layer is formed. This technical concept can not only ensure the successful preparation of the nanofiltration membrane, but also enable it to have both high permeability and high retention performance.
[0008] Preferably, the anionic polyelectrolyte layer is a finishing coating because in subsequent application environments, such as salt lakes or aqueous solution environments, cationic polyelectrolytes are more likely to swell and are less resistant to oxidation, while anionic polyelectrolytes have better properties in these aspects.
[0009] Preferably, the initial alternating coating has 1 to 10 alternating cycles, such as 1 alternating cycle, 2 alternating cycles, 3 alternating cycles, 4 alternating cycles, 5 alternating cycles, 6 alternating cycles, 7 alternating cycles, 8 alternating cycles, 9 alternating cycles or 10 alternating cycles.
[0010] Preferably, the separated alternating coating has 1 to 10 alternating cycles. For example, it can be 1 alternating cycle, 2 alternating cycles, 3 alternating cycles, 4 alternating cycles, 5 alternating cycles, 6 alternating cycles, 7 alternating cycles, 8 alternating cycles, 9 alternating cycles or 10 alternating cycles. Preferably, in the initial alternating coating, the number average molecular weight of the high molecular weight cationic polyelectrolyte is 500 to 2000 kDa. For example, it can be 500 kDa, 600 kDa, 700 kDa, 800 kDa, 900 kDa, 1000 kDa, 1100 kDa, 1200 kDa, 1300 kDa, 1400 kDa, 1500 kDa, 1600 kDa, 1700 kDa, 1800 kDa, 1900 kDa or 2000 kDa.
[0011] Preferably, the number average molecular weight of the cationic polyelectrolyte and the anionic polyelectrolyte in the alternating coating is 1 to 100 kDa, such as 5 kDa, 10 kDa, 15 kDa, 20 kDa, 25 kDa, 30 kDa, 35 kDa, 40 kDa, 45 kDa, 50 kDa, 55 kDa, 60 kDa, 65 kDa, 70 kDa, 75 kDa, 80 kDa, 85 kDa, 90 kDa, 95 kDa or 100 kDa.
[0012] Preferably, the material of the base membrane includes one or more of the following polymers: polyethersulfone, polysulfone, sulfonated polyethersulfone, sulfonated polysulfone, polyacrylonitrile, polyimide, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polybutene, polyolefin elastomer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyetherimide, polyetheretherketone, aminated polysulfone, aminated polyethersulfone, aminated polyacrylonitrile. In this application, the type and specification of the base membrane are mainly selected based on the molecular weight cutoff of the base membrane.
[0013] Generally, the initial alternating coating may be first coated to form a high molecular weight cationic polyelectrolyte layer, and then coated to form an anionic polyelectrolyte layer; or it may be first coated to form an anionic polyelectrolyte layer, and then coated to form a high molecular weight cationic polyelectrolyte layer. In a specific implementation, considering the interaction between anions and cations, in order to better achieve the bonding self-assembly effect between different layers, the coating first coated on the base film in the initial alternating coating is a coating that can self-assemble anions and cations with the base film. If the base film contains cationic groups, the initial alternating coating may be first coated to form an anionic polyelectrolyte layer; if the base film contains anionic groups, the initial alternating coating may be first coated to form a cationic polyelectrolyte layer.
[0014] The molecular weight cutoff (abbreviated as MWCO) described in this application refers to the molecular weight of a substance of known molecular weight when the base membrane has a retention rate of 90% under specific conditions. The molecular weight cutoff of the base membrane in this application refers to the molecular weight of dextran corresponding to the retention rate of 90% of dextran in dextran aqueous solution. The concentration of the dextran aqueous solution is 100 mg / L. The test pressure is 0.5 bar and the system control temperature is 25°C.
[0015] Preferably, the molecular weight cut-off of the basement membrane is 500-2000 kDa. For example, it may be 500 kDa, 600 kDa, 700 kDa, 800 kDa, 900 kDa, 1000 kDa, 1100 kDa, 1200 kDa, 1300 kDa, 1400 kDa, 1500 kDa, 1600 kDa, 1700 kDa, 1800 kDa, 1900 kDa or 2000 kDa. The basement membrane has a relatively large molecular weight cut-off, i.e., the basement membrane has a relatively large pore size. In the prior art, a basement membrane with a small pore size is often used, and a basement membrane with a relatively large pore size cannot be used to successfully prepare a high-performance nanofiltration membrane.
[0016] The base membrane for implementing the technical solution of the present application is not limited by its specific processing and forming form. Preferably, the base membrane is selected from one or more of a hollow fiber membrane, a flat membrane and a tubular membrane.
[0017] Preferably, the number average molecular weight of the anionic polyelectrolyte is 50 to 2000 kDa. In the present application, the anionic polyelectrolyte in the anionic polyelectrolyte layer in the initial alternating coating and the anionic polyelectrolyte in the anionic polyelectrolyte layer in the separated alternating coating can adopt this number average molecular weight range. Generally, the number average molecular weight of the anionic polyelectrolyte in the present application can generally be 50 kDa, 100 kDa, 200 kDa, 300 kDa, 400 kDa, 500 kDa, 600 kDa, 700 kDa, 800 kDa, 900 kDa, 1000 kDa, 1100 kDa, 1200 kDa, 1300 kDa, 1400 kDa, 1500 kDa, 1600 kDa, 1700 kDa, 1800 kDa, 1900 kDa or 2000 kDa.
[0018] Preferably, the cationic polyelectrolyte in the cationic polyelectrolyte layer is a polymer selected from at least one of a primary amine, a secondary amine, a tertiary amine or a quaternary ammonium salt group.
[0019] Preferably, the anionic polyelectrolyte in the anionic polyelectrolyte layer is a polymer selected from at least one of sulfonate, carboxylate, phosphate or nitrate.
[0020] Preferably, the cationic polyelectrolyte is selected from one or more of the following: polyacrylamine hydrochloride (PAH for short), polydimethyldiallyl ammonium chloride (PDADMAC for short), polyvinylbenzyltrimethylammonium chloride (PVBTMAC for short), polyethyleneimine (PEI for short), polydichloroethyl ether tetramethylethylenediamine, polymethacryloyloxyethyltrimethylammonium chloride (CPF for short), chitosan and polyacrylamide (PAM for short).
[0021] Preferably, the anionic polyelectrolyte is selected from one or more of the following: sodium polystyrene sulfonate, sodium dextran sulfate, sodium carboxymethyl cellulose, sodium polyacrylate, sodium polyvinyl sulfonate, sulfonated polyetheretherketone and hyaluronic acid.
[0022] Preferably, the layer-by-layer self-assembled nanofiltration membrane includes one or more of the following features:
[0023] The permeability coefficient of pure water is not less than 15L / m 2 ·h·bar;
[0024] The MgSO4 retention rate is not less than 95%.
[0025] Retention rate The second aspect of the present invention also discloses a method for preparing the layer-by-layer self-assembled nanofiltration membrane according to any of the above, first coating on the base membrane to form an initial alternating coating, and then coating to form a separation alternating coating.
[0026] In the technical solution of the present application, the concentration of the polyelectrolyte solution has little effect on the structure and performance of the nanofiltration membrane, such as the pore size. Once the cationic polyelectrolyte and the anionic polyelectrolyte are combined, the film formed will hinder the subsequent mutual combination of polyelectrolytes, and the steric hindrance generated can limit the addition of more polyelectrolytes to the polyelectrolyte multilayer film.
[0027] Preferably, when forming the initial alternating coating, the concentration of the high molecular weight cationic polyelectrolyte solution is 0.1-20 g / L. For example, it can be 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L, 10 g / L, 10.5 g / L, 11 g / L, / L, 11.5g / L, 12g / L, 12.5g / L, 13g / L, 13.5g / L, 14g / L, 14.5g / L, 15g / L, 15.5g / L, 16g / L, 16.5g / L, 17g / L, 17.5g / L, 18g / L, 18.5g / L, 19g / L, 19.5g / L or 20g / L.
[0028] Preferably, when forming the solution of the separated alternating coating, the concentration of the small molecular weight cationic polyelectrolyte solution is 1-20 g / L, such as 1 g / L, 2 g / L, 3 g / L, 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L, 10 g / L, 10.5 g / L, 11 g / L, 11.5 g / L, 12 g / L, 12.5 g / L, 13 g / L, 13.5 g / L, 14 g / L, 14.5 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L, 20 g / L.
[0029] Preferably, the concentration of anionic polyelectrolyte in the solution for forming the separated alternating coating or the initial alternating coating is 2-10 g / L, such as 2 g / L, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L, 4.5 g / L, 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L or 10 g / L.
[0030] Preferably, the solvent in the above solution is a saline solution, and the concentration of the saline solution is 0.001-3.0 mol / L. For example, it can be 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.55 mol / L, 0.6 mol / L, 0.65 mol / L, 0.7 mol / L, 0.75 mol / L, 0.8 mol / L, 0.9 mol / L, 0.95 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L. Preferably, the concentration of the saline solution is 0.05-1.0 mol / L. The salt is selected from one or more of NaCl, NaNO3, NaBr, NaAc, NaF, NaBr, KCl, KBr, Na2SO4 and MgCl2.
[0031] The third invention of the present invention also discloses the use of any of the above-mentioned layer-by-layer self-assembled nanofiltration membranes for removing small organic molecule pollutants in water.
[0032] The fourth aspect of the present invention also discloses the use of any of the above-mentioned layer-by-layer self-assembled nanofiltration membranes for extracting lithium from salt lakes.
[0033] As described above, the layer-by-layer self-assembled nanofiltration membrane and its preparation method and use of the present invention have the following beneficial effects:
[0034] 1. In practice, the applicant found that for base membranes with MWCO of 500 kDa and above, it is impossible to prepare a NF membrane with retention performance by using a small molecular weight polyelectrolyte with a molecular weight of less than 5 kDa alone. However, a NF membrane with excellent retention performance can be prepared by using a large molecular weight polyelectrolyte with a molecular weight of not less than 500 kDa, that is, a cationic polyelectrolyte with a large molecular weight (number average molecular weight not less than 500 kDa) is first coated on the base membrane with a large pore size to fill the pores, and then a small molecular weight polyelectrolyte (number average molecular weight not exceeding 100 kDa) is used to fill and reduce the pore size of the coating, thereby proposing the technical solution claimed for protection in this application.
[0035] 2. The permeability of the layer-by-layer self-assembled nanofiltration membrane provided by the present invention is much higher than that of the polyelectrolyte layer-by-layer self-assembled NF membrane reported in current patents and literature. The layer-by-layer self-assembled polyelectrolyte NF membrane has both high porosity and small pore size.
[0036] 3. Compared with existing commercial nanofiltration membranes and the current mainstream layer-by-layer self-assembly nanofiltration membrane preparation technology, it has better permeability and micro-pollutant retention rate, and the process operation method is simple, and the membrane structure and properties are easy to control. Compared with conventional processes for preparing nanofiltration membranes and reverse osmosis membranes such as interfacial polymerization, this technology is more flexible, non-toxic, harmless, green and environmentally friendly, and has a lower cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Pure water permeability coefficient and retention rate of 500 ppm MgSO4 of the nanofiltration membrane prepared in Examples 1-4.
[0038] Figure 2 Pure water permeability coefficient and retention rate of 500 ppm MgSO4 of the nanofiltration membranes prepared in Comparative Examples 1-4.
[0039] Figure 3 Magnesium-lithium separation coefficient of the nanofiltration membrane prepared in Examples 1-4 and Comparative Examples 1-4.
[0040] Figure 4 The retention rates of the nanofiltration membranes prepared in Examples 1-4 and Comparative Examples 1-4 for micropollutants. DETAILED DESCRIPTION
[0041] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0042] The term "coating" used in this article should be understood in a broad sense, and can be any means that can make at least two substances be coated, bonded or connected together in a physical or chemical reaction, for example, one layer can be coated on another layer under appropriate conditions, or one layer can be immersed in another layer. The coating in this application can be brush coating, roller coating, spray coating, dip coating, spin coating, screen printing, filter pressing or curtain coating, etc.
[0043] In this article, the term "base membrane" refers to a self-supporting or externally supported membrane material, which can be a hollow fiber membrane, a flat plate or a tubular type. Anyone with basic knowledge of membrane preparation can prepare any form and membrane material according to the method provided by the present invention.
[0044] In the present application, the term "cationic polyelectrolyte layer" refers to a coating layer formed by a cationic polyelectrolyte material. The cationic polyelectrolyte refers to a high molecular polymer that can ionize cations in an aqueous solution. The polymer is a water-soluble polymer with a positive ion group on the main chain or side chain.
[0045] In this application, the term "anionic polyelectrolyte layer" refers to a coating formed by anionic polyelectrolyte materials, wherein the anionic polyelectrolyte refers to a water-soluble polymer whose majority of molecules can be ionized into polymer ions and many small molecular ions (counter ions) when dissolved in water. Anionic polyelectrolytes carry proton-accepting groups, and common anionic groups include -COO^-, -SO3^-, -O-CS2^-, -O-PO3 ^2 -wait.
[0046] These polyelectrolytes have properties similar to those of electrolytes (salts) and polymers (high molecular weight compounds) and are sometimes called polysalts. Like salts, their solutions are conductive, and like polymers, their solutions are usually viscous.
[0047] In this application, the retention rate (R) is defined as: under certain conditions, the concentration of the raw material solution (C f ) and the permeate concentration (C p ) difference, and then divided by the raw material solution concentration (C f ), R=(C f -C p ) / C f The test conditions for the retention rate of the layer-by-layer self-assembled nanofiltration membrane of the present invention are as follows: A) The retention rate for magnesium sulfate: 500 mg / L (corresponding to 500 ppm) magnesium sulfate salt solution concentration, the test pressure is 3 bar,
[0048] The system controlled temperature was 25°C;
[0049] B) For organic small molecules: an aqueous solution containing six micropollutants, namely, testosterone, tetracycline, oxytetracycline, sulfadiazine, sulfamethoxazole and norfloxacin, is used, and the content of each specific organic small molecule is 200 ppb;
[0050] The test pressure is 3 bar and the system control temperature is 25°C.
[0051] In this application, the magnesium-lithium separation coefficient (S) is defined as: under certain conditions, the Mg permeate (p) 2+ and Li + The ratio of the concentration of Mg on the feed liquid side (f) is divided by 2+ and Li + The ratio of the concentration of S Mg,Li =(C Li+ / C Mg 2+ ) p / (C Li+ / C Mg 2+ ) f =(1-R Li+ ) / (1-R Mg 2+ ). The test conditions for the magnesium-lithium separation coefficient of the layer-by-layer self-assembled nanofiltration membrane of the present invention are that the concentration of the mixed salt solution is 2000-6000 mg / L (corresponding to 2000-6000 ppm), the mass ratio of magnesium to lithium is 20-60, the test pressure is 2.0-4.0 bar, and the system control temperature is 25°C. In a more specific test example, the test pressure is 4 bar, the mass ratio of magnesium ions to lithium ions is 20, a mixed solution formed by magnesium chloride and lithium chloride is selected, and the concentration of the mixed salt solution is 2000 ppm.
[0052] In this application, the permeability coefficient J is defined as: the mass flowing out per unit area per unit time under certain conditions. J = Δm / (ρAΔt P), where Δm (kg) is the mass increment of the filtrate during the separation time Δt (h), and ρ is the density of the filtrate (1kg L -1 ), A(m 2 ) is the effective filtration area, P (bar) is the transmembrane pressure. The system control temperature is room temperature such as 25°C (the same below).
[0053] In the more specific embodiments and comparative examples illustrated below in the present application, the specific coating method is: the hollow fiber membrane is formed into a membrane assembly, and then the relevant solutions for forming the initial alternating coating are introduced into the through holes thereof, and then the relevant solutions for forming the separation alternating coating are introduced.
[0054] In a more specific embodiment, the following steps are included: after the hollow fiber membrane base membrane is backwashed with pure water for pre-cleaning, a high molecular weight cationic polyelectrolyte solution is first introduced into the hollow inner cavity of the hollow fiber membrane and allowed to stand; the inside of the base membrane is cleaned with pure water, and the inside of the membrane is purged with 0.5 bar nitrogen; in the same way, an anionic polyelectrolyte solution is introduced into the hollow inner cavity, and the pure water is washed and then the nitrogen is purged, and the initial alternating coating ends here; then the separation alternating coating is formed in the same way. More specifically, the separation alternating coating has two cycles, thereby completing a total of 3 alternating cycles of coating.
[0055] Example 1
[0056] In this specific embodiment, in the specific layer-by-layer self-assembled nanofiltration membrane:
[0057] Base membrane: polyethersulfone hollow fiber membrane with molecular weight cutoff (MWCO) of 500 kDa;
[0058] Initial alternating coatings: cationic polyelectrolyte polydimethyldiallyl ammonium chloride (PDADMAC) with a number average molecular weight of 600 kDa and anionic polyelectrolyte sodium polystyrene sulfonate (PSS) with a number average molecular weight of 1000 kDa;
[0059] Separate alternating coatings: anionic polyelectrolyte sodium polystyrene sulfonate (PSS) with a number average molecular weight of 1000 kDa and cationic polyelectrolyte polydimethyldiallylammonium chloride (PDADMAC) with a number average molecular weight of 5 kDa.
[0060] The polyelectrolytes mentioned above were respectively dissolved in a 0.5 mol / L sodium chloride background solution to prepare a coating solution with a polyelectrolyte concentration of 0.02 mol / L.
[0061] After the base membrane is backwashed with pure water for pre-cleaning, a PDADMAC solution with a number average molecular weight of 600 kDa is first introduced into the hollow inner cavity of the hollow fiber membrane and allowed to stand; the inside of the base membrane is cleaned with pure water; the PSS solution is introduced into the hollow inner cavity in the same way, and nitrogen is purged after pure water cleaning, and the initial alternating coating ends here. Then, a separation alternating coating is formed in the same way, in which the cationic polyelectrolyte solution is replaced with a PDADMAC solution with a number average molecular weight of 5 kDa, and the PSS solution remains unchanged. The separation alternating coating has two cycles, thereby completing a total of 3 alternating cycles of coating.
[0062] The nanofiltration membrane is formed by the above. The following is the test of the nanofiltration membrane.
[0063] Prepare 500ppm MgSO4 solution and test the integrity of the NF membrane separation layer at 3bar.
[0064] Six micropollutant solutions of testosterone, tetracycline, oxytetracycline, sulfadiazine, sulfamethoxazole and norfloxacin were prepared with contents of 200 ppb respectively, and the MPs retention rate of the NF membrane in Example 1 was tested at 3 bar.
[0065] The test results are: pure water permeability coefficient 16.8L / m 2 ·h·bar, the retention rate for MgSO4 is 96.8%, the retention rate for testosterone, tetracycline, oxytetracycline and sulfadiazine is 100%, the retention rate for sulfamethoxazole is 99.3%, and the retention rate for norfloxacin is 99.7%.
[0066] Preparation of simulated salt lake brine solution: 2000ppm MgCl2 / LiCl mixed solution as raw material solution, of which Mg 2+ / Li + The mass ratio is 20. The nanofiltration membrane in Example 1 was tested at a test pressure of 4 bar. The test results are: the permeability coefficient is 17.1 L / m 2 ·h·bar,Mg 2+ The retention rate of Li + The retention rate is 8.6%, and the magnesium-lithium separation coefficient S is 102.
[0067] Example 2
[0068] In this specific embodiment, in the specific layer-by-layer self-assembled nanofiltration membrane:
[0069] Base membrane: polyethersulfone hollow fiber membrane with MWCO of 500 kDa was selected;
[0070] Initial alternating coating: PDADMAC with a molecular weight of 600 kDa was selected as the cationic polyelectrolyte, and PSS with a molecular weight of 1000 kDa was selected as the anionic polyelectrolyte;
[0071] Separation alternating coating: the cationic polyelectrolyte is PDADMAC with a molecular weight of 100 kDa, and the anionic polyelectrolyte is PSS with a molecular weight of 100 kDa.
[0072] The coating method and testing method are the same as in Example 1.
[0073] The results showed that the nanofiltration membrane prepared in Example 2 had a pure water permeability coefficient of 16.2 L / m 2 ·h·bar, the retention rate of MgSO4 is 97.6%, and the retention rates of testosterone, tetracycline, oxytetracycline, sulfadiazine, sulfamethoxazole and norfloxacin are all 100%. 2+ The retention rate of Li is 99.2%. + The retention rate is 8.8%, and the magnesium-lithium separation coefficient S is 114.
[0074] Example 3
[0075] In this specific embodiment, in the specific layer-by-layer self-assembled nanofiltration membrane:
[0076] Base membrane: polyethersulfone hollow fiber membrane with MWCO of 500 kDa was selected;
[0077] Initial alternating coating: PDADMAC with a molecular weight of 600 kDa was selected as the cationic polyelectrolyte, and PSS with a molecular weight of 1000 kDa was selected as the anionic polyelectrolyte;
[0078] Separation alternating coating: PAH with a molecular weight of 20 kDa is selected as the cationic polyelectrolyte, and PSS with a molecular weight of 1000 kDa is selected as the anionic polyelectrolyte.
[0079] The coating method and testing method are the same as in Example 1.
[0080] The results showed that the nanofiltration membrane prepared in Example 3 had a pure water permeability coefficient of 15.6 L / m 2 ·h·bar, the retention rate of MgSO4 is 99.1%, and the retention rates of testosterone, tetracycline, oxytetracycline, sulfadiazine, sulfamethoxazole and norfloxacin are all 100%. 2+The retention rate of Li + The retention rate is 8.2%, and the magnesium-lithium separation coefficient S is 131.
[0081] Example 4
[0082] In this specific embodiment, in the specific layer-by-layer self-assembled nanofiltration membrane:
[0083] Base membrane: polyethersulfone hollow fiber membrane with MWCO of 500 kDa was selected;
[0084] Initial alternating coating: PDADMAC with a molecular weight of 600 kDa was used as the cationic polyelectrolyte, and PSS with a molecular weight of 1000 kDa was used as the anionic polyelectrolyte;
[0085] Separation alternating coating: PAH with a molecular weight of 20 kDa is selected as the cationic polyelectrolyte, and PSS with a molecular weight of 100 kDa is selected as the anionic polyelectrolyte.
[0086] The coating method and testing method are the same as in Example 1.
[0087] The results showed that the nanofiltration membrane prepared in Example 4 had a pure water permeability coefficient of 15.2 L / m 2 ·h·bar, the retention rate of MgSO4 is 99.4%, and the retention rates of testosterone, tetracycline, oxytetracycline, sulfadiazine, sulfamethoxazole and norfloxacin are all 100%. 2+ The retention rate of Li + The retention rate is 12.4%, and the magnesium-lithium separation coefficient S is 146.
[0088] Example 5
[0089] The only difference between this embodiment and embodiment 1 is that the molecular weight cutoff of the base membrane is different. In this embodiment, the base membrane adopts a polyethersulfone hollow fiber membrane with a MWCO of 1200 kDa. The rest is the same as embodiment 1.
[0090] The test results show that the pure water permeability coefficient is 18.4L / m 2 ·h·bar, the rejection rate of MgSO4 is 95.4%;
[0091] The removal rates of tetracycline, oxytetracycline and sulfadiazine were 100%, the removal rates of testosterone were 99.1%, the removal rates of sulfamethoxazole were 98.6%, and the removal rates of norfloxacin were 99.2%;
[0092] Mg 2+ The retention rate of Li + The retention rate is 4.3%, and the magnesium-lithium separation coefficient S is 87.
[0093] Example 6
[0094] The only difference between this embodiment and embodiment 1 is that the molecular weight cutoff of the base membrane is different. In this embodiment, the base membrane adopts a polyethersulfone hollow fiber membrane with a MWCO of 1800 kDa. The rest is the same as embodiment 1.
[0095] The test results show:
[0096] Pure water permeability coefficient 19.2L / m 2 ·h·bar, the rejection rate of MgSO4 is 95.1%;
[0097] The removal rates of tetracycline and oxytetracycline were 100%, testosterone was 98.8%, sulfamethoxazole was 98.1%, sulfadiazine was 99.3%, and norfloxacin was 98.7%;
[0098] Mg 2+ The retention rate of Li + The retention rate is 2.1% and the magnesium-lithium separation coefficient S is 75.
[0099] Example 7
[0100] The only difference between this embodiment and embodiment 1 is that the material of the base membrane is different. In this embodiment, the base membrane adopts a polysulfone hollow fiber membrane with a MWCO of 600Da, and the rest is the same as embodiment 1.
[0101] The test results show:
[0102] Pure water permeability coefficient 15.7L / m 2 ·h·bar, the interception rate of MgSO4 is 97.1%,
[0103] The removal rates of tetracycline, oxytetracycline and sulfadiazine were 100%, the removal rates of testosterone were 99.4%, the removal rates of sulfamethoxazole were 98.7%, and the removal rates of norfloxacin were 99.2%;
[0104] Mg 2+ The retention rate of Li + The retention rate is 7.8%, and the magnesium-lithium separation coefficient S is 102.
[0105] Example 8
[0106] The only difference between this embodiment and embodiment 1 is that the material of the base membrane is different. In this embodiment, the base membrane adopts a polyacrylonitrile hollow fiber membrane with a MWCO of 800Da, and the rest is the same as embodiment 1.
[0107] The test results show:
[0108] Pure water permeability coefficient 16.2L / m2 ·h·bar, the interception rate of MgSO4 is 97.1%,
[0109] The removal rates of tetracycline and oxytetracycline were 100%, testosterone was 99.0%, sulfamethoxazole was 98.9%, sulfadiazine was 99.2%, and norfloxacin was 98.7%;
[0110] Mg 2+ The retention rate of Li is 99.2%. + The retention rate is 6.4%, and the magnesium-lithium separation coefficient S is 117.
[0111] Example 9
[0112] The only difference between this embodiment and embodiment 2 is that the molecular weight of the cationic polyelectrolyte in the initial alternating coating is changed, and 1000 kDa PDADMAC is used. The rest is the same as embodiment 2.
[0113] The test results show:
[0114] Pure water permeability coefficient 16.4L / m 2 ·h·bar, the interception rate of MgSO4 is 97.0%,
[0115] The removal rates of testosterone, tetracycline, oxytetracycline, sulfadiazine, sulfamethoxazole and norfloxacin were all 100%;
[0116] Mg 2+ The retention rate of Li + The retention rate is 5.7% and the magnesium-lithium separation coefficient S is 105.
[0117] Example 10
[0118] The only difference between this embodiment and embodiment 2 is that the molecular weight of the cationic polyelectrolyte in the initial alternating coating is changed, and 1500 kDa PDADMAC is used. The rest is the same as embodiment 2.
[0119] The test results show:
[0120] Pure water permeability coefficient 16.0L / m 2 ·h·bar, the interception rate of MgSO4 is 96.6%,
[0121] The removal rates of testosterone, tetracycline, oxytetracycline, sulfadiazine, sulfamethoxazole and norfloxacin were all 100%;
[0122] Mg 2+ The retention rate of Li + The retention rate is 5.2%, and the magnesium-lithium separation coefficient S is 94.8.
[0123] Embodiment 11
[0124] The difference between this embodiment and embodiment 2 lies in: the change of cationic polyelectrolyte in the initial alternating coating and the separation alternating coating, specifically: 1) 800 kDa PAH is used in the initial alternating coating; 2) 100 kDa PAH is used in the separation alternating coating; the rest are the same as embodiment 2.
[0125] The test results show:
[0126] Pure water permeability coefficient 15.1L / m 2 ·h·bar, the interception rate of MgSO4 is 99.2%,
[0127] The removal rates of testosterone, tetracycline, oxytetracycline, sulfadiazine, sulfamethoxazole and norfloxacin were all 100%;
[0128] Mg 2+ The retention rate of Li + The retention rate is 10.2%, and the magnesium-lithium separation coefficient S is 150.
[0129] Example 12
[0130] The difference between this embodiment and embodiment 2 lies in: the change of cationic polyelectrolyte in the initial alternating coating and the separation alternating coating, specifically: 1) 800 kDa PVBTMAC is used in the initial alternating coating; 2) 100 kDa PAH is used in the separation alternating coating; the rest is the same as embodiment 2.
[0131] The test results show:
[0132] Pure water permeability coefficient 20.6L / m 2 ·h·bar, the interception rate of MgSO4 is 95.1%,
[0133] The removal rates of testosterone, tetracycline, oxytetracycline, sulfadiazine, sulfamethoxazole and norfloxacin were all 100%;
[0134] Mg 2+ The retention rate of Li + The retention rate is 6.7% and the magnesium-lithium separation coefficient S is 104.
[0135] Comparative Example 1
[0136] This comparative example is a comparative example of Example 1.
[0137] The coating method and the test method are the same as those in Example 1, except that the initial alternating coating as in Example 1 is not used, but the initial alternating coating in the example is replaced by the separation alternating coating to form 3 cycles of alternating coating. Specifically, 5 kDa PDADMAC and 1000 kDa PSS are used in a polyethersulfone hollow fiber porous support membrane with a MWCO of 500 kDa.
[0138] The results showed that the pure water permeability coefficient of the prepared nanofiltration membrane was 51.8L / m 2 ·h·bar, the retention rate of MgSO4 is 9.8%, and the retention rates of testosterone, tetracycline, oxytetracycline, sulfadiazine, sulfamethoxazole and norfloxacin are all less than 20%. 2+ The retention rate of Li + The rejection rate is 2.8% and the magnesium-lithium separation coefficient S is 1.08.
[0139] Comparative Example 2
[0140] This comparative example is a comparative example of Example 1.
[0141] The coating method and the test method are the same as those in Example 1, except that the separation alternating coating is not formed by the small molecular weight cationic polyelectrolyte as in Example 1, but the initial alternating coating as in Example 1 is used. Specifically, three periodic layers of coating are performed on a polyethersulfone hollow fiber porous support membrane with a MWCO of 500 kDa using 600 kDa PDADMAC and 1000 kDa PSS.
[0142] The results showed that the pure water permeability coefficient of the prepared nanofiltration membrane was 16.6L / m 2 ·h·bar, the retention rate of MgSO4 is 90.6%, the retention rate of tetracycline and oxytetracycline is 100%, the retention rate of testosterone is 91.4%, the retention rate of norfloxacin is 83.7%, the retention rate of sulfadiazine is 72.6%, and the retention rate of sulfamethoxazole is 68.9%. Mg 2+ The retention rate of Li + The rejection rate is 7.4% and the magnesium-lithium separation coefficient S is 44.10.
[0143] Comparative Example 3
[0144] The coating method and the testing method were the same as those in Example 1, and three cycles of coating were performed on a polyethersulfone hollow fiber porous support membrane with a MWCO of 100 kDa using 5 kDa PDADMAC and 1000 kDa PSS.
[0145] The results showed that the pure water permeability coefficient of the prepared nanofiltration membrane was 8.7L / m 2·h·bar, the retention rate of MgSO4 is 93.0%, the retention rate of testosterone, tetracycline, oxytetracycline and norfloxacin is 100%, the retention rate of sulfadiazine is 99.2%, and the retention rate of sulfamethoxazole is 99.5%. Mg 2+ The retention rate of Li is 99.2%. + The rejection rate is 12.4%. The magnesium-lithium separation coefficient S is 109.5.
[0146] Comparative Example 4
[0147] The coating method and the testing method were the same as those in Example 1, and three cycles of coating were performed on a polyethersulfone hollow fiber porous support membrane with a MWCO of 100 kDa using 600 kDa PDADMAC and 1000 kDa PSS.
[0148] The results showed that the pure water permeability coefficient of the prepared nanofiltration membrane was 9.1 L / m 2 ·h·bar, the retention rate of MgSO4 is 92.3%, the retention rate of tetracycline, oxytetracycline and norfloxacin is 100%, the retention rate of testosterone is 98.2%, the retention rate of sulfadiazine is 97.4%, and the retention rate of sulfamethoxazole is 95.6%. Mg 2+ The retention rate of Li + The rejection rate is 8.2%. The magnesium-lithium separation coefficient S is 48.32.
[0149] Through Examples 1-4, the water permeability and micropollutant retention rate data of the nanofiltration membrane obtained by the test were compared. The water permeability coefficient obtained by the technical solution of the present invention is as high as 15L / m 2 ·h·bar, the rejection rate of micropollutants with a molecular weight cutoff of more than 200Da is more than 99%, and the magnesium-lithium separation coefficient is not less than 100. It is further proved that by alternately coating a large molecular weight polyelectrolyte solution on the surface of a large-pore, high-porosity base membrane, and then coating a small molecule polyelectrolyte, the water permeability coefficient of the nanofiltration membrane can be significantly improved, while ensuring a high micropollutant rejection rate, providing a good choice for nanofiltration membranes to efficiently remove micropollutants from surface water.
[0150] Therefore, the present invention effectively overcomes various shortcomings in the prior art and has high industrial utilization value.
[0151] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A layer-by-layer self-assembled nanofiltration membrane, characterized in that: The layer-by-layer self-assembled nanofiltration membrane includes a base membrane and a self-assembled coating formed on the base membrane, wherein the self-assembled coating includes at least an initial alternating coating and a separation alternating coating; the cutoff molecular weight of the base membrane is not less than 500kDa; the initial alternating coating is an alternating assembly of a large molecular weight cationic polyelectrolyte layer and an anionic polyelectrolyte layer, and the separation alternating coating is an alternating assembly of a small molecular weight cationic polyelectrolyte layer and an anionic polyelectrolyte layer; the initial alternating coating is formed on the base membrane, and the large molecular weight cationic polyelectrolyte layer in the initial alternating coating is a cationic polyelectrolyte with a number average molecular weight of not less than 500kDa; the small molecular weight cationic polyelectrolyte layer in the separation alternating coating is a cationic polyelectrolyte with a number average molecular weight not exceeding 100kDa.
2. The layer-by-layer self-assembled nanofiltration membrane according to claim 1, characterized in that: The anionic polyelectrolyte layer is a finishing coating; and / or, the separated alternating coatings have 1 to 10 alternating cycles; and / or, in the initial alternating coating, the number average molecular weight of the high molecular weight cationic polyelectrolyte is 500 to 2000 kDa; and / or, in the separation alternating coating, the number average molecular weight of the small molecular weight cationic polyelectrolyte is 1 to 100 kDa; And / or, the number average molecular weight of the anionic polyelectrolyte is 50 to 2000 kDa.
3. The layer-by-layer self-assembled nanofiltration membrane according to claim 1, characterized in that: The material of the base membrane includes one or more of the following polymers: polyethersulfone, polysulfone, sulfonated polyethersulfone, sulfonated polysulfone, polyacrylonitrile, polyimide, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polybutene, polyolefin elastomer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyetherimide, polyetheretherketone, aminated polysulfone, aminated polyethersulfone, and aminated polyacrylonitrile.
4. The layer-by-layer self-assembled nanofiltration membrane according to claim 1, characterized in that: The molecular weight cut-off of the basement membrane is 500-2000 kDa; and / or, the base membrane is selected from one or more of a hollow fiber membrane, a flat membrane and a tubular membrane; and / or, the cationic polyelectrolyte in the cationic polyelectrolyte layer is a polymer selected from at least one of a primary amine, a secondary amine, a tertiary amine or a quaternary ammonium salt group; And / or, the anionic polyelectrolyte in the anionic polyelectrolyte layer is a polymer selected from at least one of sulfonate, carboxylate, phosphate or nitrate.
5. The layer-by-layer self-assembled nanofiltration membrane according to claim 4, characterized in that: The cationic polyelectrolyte is selected from one or more of the following: polyacrylamine hydrochloride, polydimethyldiallyl ammonium chloride, polyvinylbenzyltrimethylammonium chloride, polyethyleneimine, polydichloroethyl ether tetramethylethylenediamine, methacryloyloxyethyltrimethylammonium chloride, chitosan and polyacrylamide; And / or, the anionic polyelectrolyte is selected from one or more of the following: sodium polystyrene sulfonate, sodium dextran sulfate, sodium carboxymethyl cellulose, sodium polyacrylate, sodium polyvinyl sulfonate, sulfonated polyetheretherketone and hyaluronic acid.
6. The layer-by-layer self-assembled nanofiltration membrane according to claim 1, characterized in that: The layer-by-layer self-assembled nanofiltration membrane includes one or more of the following features: a) The permeability coefficient of pure water is not less than 15L / m 2 ·h·bar; b) The MgSO4 retention rate is not less than 95%.
7. A method for preparing a layer-by-layer self-assembled nanofiltration membrane according to any one of claims 1 to 6, characterized in that: The base film is first coated to form an initial alternating coating, and then coated to form a separate alternating coating.
8. The preparation method according to claim 7, characterized in that: When forming the high molecular weight cationic polyelectrolyte layer in the initial alternating coating, the concentration of the high molecular weight cationic polyelectrolyte solution is 0.1 to 20 g / L; and / or, when forming the small molecular weight cationic polyelectrolyte layer in the separated alternating coating, the concentration of the small molecular weight cationic polyelectrolyte solution is 1 to 20 g / L; and / or, when forming the anionic polyelectrolyte layer in the initial alternating coating or the separating alternating coating, the concentration of the anionic polyelectrolyte solution is 2 to 10 g / L; And / or, the solvent used to form the initial alternating coating or the separated alternating coating is a saline solution, the concentration of the saline solution is 0.001 mol / L-3.0 mol / L, and the salt is selected from one or more of NaCl, NaNO3, NaBr, NaAc, NaF, NaBr, KCl, KBr, Na2SO4 and MgCl2.
9. Use of the layer-by-layer self-assembled nanofiltration membrane as claimed in any one of claims 1 to 6 for removing small organic molecule pollutants in water.
10. Use of the layer-by-layer self-assembled nanofiltration membrane as claimed in any one of claims 1 to 6 for extracting lithium from salt lakes.
Citation Information
Patent Citations
Method for producing polyelectrolyte self-assembly composite nanofiltration membrane
CN102580550B
Preparation method of polyelectrolyte self-assembled composite nonafiltration membrane based on coordination
CN102688701A
Method for preparing composite nanofiltration membrane
CN101053780A
Nanofiltration membrane as well as preparation method and application thereof
CN104548970A
High-permeability selective acid-resistant nanofiltration membrane material as well as preparation method and application thereof
CN113332859A
Cited By
TPU mobile phone shell capable of improving silk-screen precision and preparation method of TPU mobile phone shell
CN120329708A
TPU mobile phone case with improved silk printing precision and preparation method thereof
CN120329708B
Preparation method of polyelectrolyte dip-coated covalent organic framework nanofiltration membrane
CN120733582A
Self-assembled composite coating film for removing antibiotics in wastewater and preparation method of self-assembled composite coating film
CN120900447A